Transformasi Digital dan Keberlanjutan Operasional Usaha Mikro dan Kecil: Studi Literatur - Rifqi Soedjono, Muhammad; Wibawa, Berto Mulia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to systematically review operational and production management practices in Micro and Small Enterprises in developing countries using the Systematic Literature Review method and PRISMA guidelines. A total of 52 articles published between 2016 and 2025 were analyzed from the Scopus database. The literature synthesis identified six main themes, namely digital transformation and technology adoption, green and sustainable operations, quality management and lean production, innovation capabilities and entrepreneurial leadership, circular economy and green supply chains, as well as research challenges and gaps. The analysis results show that SME operational management practices in developing countries have moved towards more efficient, innovative, and sustainability-oriented systems. Internal factors such as digital literacy, innovation capabilities, and entrepreneurial leadership play an important role in improving production performance, while external factors such as policy support, digital infrastructure, and cross-actor collaboration are the main catalysts. This research provides theoretical and practical contributions to understanding the dynamics of digital transformation and operational sustainability of SMEs in the era of the green economy.